Politique de la rue et politique des urnes - Ожьен, Альбер (Социологическое обозрение, 2014)
The “Arab Spring” uprisings have unexpectedly led to a strikingly fast and worldwide movement of opposition to governments and economic powers. This sudden and unpredictable outbreak of protest has given birth to a new form of political action, which may be called “gatherings”, i.e. people taking to the streets and occupying squares to claim a radical change of the political order through demands for a better or renewed democracy. Gatherings are innovative as they arise outside traditional ways of expressing political grievances (i.e. through parties, trade unions, NGOs and associations), have neither leader nor program, advocate non violence and disavow the system of representative government. This new way to practice street politics opposes ballot box politics as it claims direct democracy (general assemblies, open meetings, no decision by a majority, equally shared responsibilities, transparency, etc.) while ardently endorsing non violence. This commitment is contentious: how can one pretend toppling the rule of the rich and the powerful who benefit from an entrenched system of domination without making use of violence to oust them from their privileged position? This article aims at clarifying the terms of this question by exploring the way resorting to violence has been debated in many of these gatherings.